A fourteen year unconsummated marriage and its successful treatment (a case report) - N Mirzaie; AT Saremi (JRI, 2002)
Unconsummated marriage (UCM) is defined as a marriage with no intercourse action. Different etiologies have been introduced as the causative agents including psychiatric, social and physical factors. The reported couple had under gone treatment due to 14 years history of UCM and wanting a child. During marriage and UCM follow up the wife had undertaken multiple surgeries for cervical dilatation, myomectomy, electrocautery and a course of psychotherapy. According to their please to have a child, 10 times IUI had been performed which were unsuccessful. Approximately after psychiatric assessment, couples were treated by sex therapy methods and then individual psychotherapy was performed for wife to reduce anxiety. After 5 months, pregnancy occurred via normal intercourse, which resulted in a term delivery. Combination of couple sex therapy and individual psychotherapy haven’t been used before to treat UCM. Other methods such as dual sex therapy, hypno-behavioral therapy and psychosomatic therapy have been used separately or in combination with urology and gynecologic treatments. Since inadequate knowledge about sexual relationship and dependency to paternal family are of the most important and frequent reasons of this disorder, it seems sexual relation education in educational and health centers in our country is necessary.
Keywords: Unconsummated marriage, Sex therapy, Psychotherapy, Infertility